Joyless Laughter: Thaumazein at a World on Fire - Rodríguez-Paniagua, Augusto (International Review of Theoretical Psychologies, 2026)
Why theorize about political humor in a world that appears to have lost its mind? I argue that humorous laughter makes it possible to think beyond the ordinary by producing an experience of alienation from everyday habits and customs that would otherwise go unquestioned. However, this same possibility might lead to anxiety and awe that pushes us to quickly resolve and conceal the contingency of our habits shown when we laugh at them. This double-facedness of the potentiality of humor and laughter is related to the philosophical concept of thaumazein - wonder and awe produced when the obvious is suddenly seen as lacking any self-evident reason for being the way it is. I argue that in order to grasp the various functions that humor and laughter can perform, it is necessary to develop an ironic consciousness that is able to avoid falling into the trap of nihilistic relativization, but also to avoid the ideal of constructing knowledge that closes the door to all kinds of ambiguities and contradictions. In this way, the study of political humor, even in its extreme and reactionary forms, can help us to understand the ways in which common sense is contested and constructed collectively.